2022
DOI: 10.1155/2022/5779276
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Camera External Validation for Artificial Intelligence Software in Diagnosis of Diabetic Retinopathy

Abstract: Aims. To investigate the applicability of deep learning image assessment software VeriSee DR to different color fundus cameras for the screening of diabetic retinopathy (DR). Methods. Color fundus images of diabetes patients taken with three different nonmydriatic fundus cameras, including 477 Topcon TRC-NW400, 459 Topcon TRC-NW8 series, and 471 Kowa nonmyd 8 series that were judged as “gradable” by one ophthalmologist were enrolled for validation. VeriSee DR was then used for the diagnosis of referable DR acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[18] DR is related with blood glucose, body mass index, and renal function. [19,20] Nowadays, some medical options have been made to treat DR including vitrectomy and photocoagulation, the prognosis is still not ideal due to unexpected side effects in DR. [21,22] Hence, it is of great significance to discover a new medical application against DR. In this study, we found BMSCsderived exosomes could alleviate HG-induced dysfunction in ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[18] DR is related with blood glucose, body mass index, and renal function. [19,20] Nowadays, some medical options have been made to treat DR including vitrectomy and photocoagulation, the prognosis is still not ideal due to unexpected side effects in DR. [21,22] Hence, it is of great significance to discover a new medical application against DR. In this study, we found BMSCsderived exosomes could alleviate HG-induced dysfunction in ARPE-19 cells.…”
Section: Discussionmentioning
confidence: 99%